Short Communication: Impact of Viral Load Use on Treatment Switch in Perinatally HIV-Infected Children in Asia - Thahira Jamal Mohamed (2018)
© 2017, Mary Ann Liebert, Inc. 2017. We sought to assess the impact of routine HIV viral load (VL) monitoring on the incidence of switching from a first- to a second-line antiretroviral therapy (ART) regimen, and to describe factors associated with switch. Data from a regional cohort of 16 clinical programs in six Asian countries were analyzed. Second-line switch was defined as a change from a non-nucleoside reverse transcriptase inhibitor (NNRTI) to a protease inhibitor (PI) or vice versa, and ≥1 of the following: (1) reported treatment failure by local criteria, (2) switch of ≥1 additional drug, or (3) a preceding HIV VL ≥1,000 copies/ml. Routine VL was having ≥1 test after ≥24 weeks of ART and ≥1 time/year thereafter. Factors associated with time to switch were evaluated with death and loss to follow-up as competing risks. A total of 2,398 children were included in this analysis. At ART initiation, the median (interquartile range) age was 6.0 (3.3-8.9) years, more than half had WHO stage 3 or 4, the median CD4 was 189 (47-456) cells/mm3, 93% were on NNRTI-based first-line ART, and 34% had routine VL monitoring. Treatment switch occurred in 17.6% of patients, at a median of 35 (22-49) months. After adjusting for country, sex, first ART regimen, and CD4% at ART initiation, children with routine VL monitoring were 1.46 (95% confidence interval 1.11-1.93) times more likely to be switched (p = .007). Scale-up of VL testing will lead to earlier identification of treatment failure, and it can help guide earlier switches to prevent resistance.